Unitarian Universalist Church of Fresno "Love is a Magic Pony" and Cupcake Making - Watkins, Howard::::::::: (1988)
Adam Watkins and Brandon Wright mixing cupcake mix; Robin Watkins and Marcy Spaulding behind them